Penguatan Soft Skill Mahasiswa Via Media Digital sebagai Kecakapan Abad 21 Perspektif Ilmu Pendidikan Islam - Moh Faizin; Azzahra Qur'ani Putri; Aisyah Alifiah Muzakki; Devina Elvaretta Arrazaq (Journal on Education, 2023)
This article we created is intended to explain about Strengthening Student Soft Skills Through Digital Media as Skills in the 21st Century from the Perspective of Islamic Education. In the world of lectures, soft skills for every student are needed to produce graduates who are ready to enter the world of work. Therefore, tertiary institutions are expected to be able to develop student soft skills to face the world of work. This can be through Digital Media. The success of a person in education is determined by the soft skills he has. Soft skills can include communication skills, empathy, honesty, courtesy, emotional intelligence, self-confidence, humility, critical thinking and everything that is subjective. It would be nice for students to participate in developing their soft skills in order to create the next generation that is useful for the nation.